MiRNA in atopic dermatitis - Rożalski, Michał; Rudnicka, Lidia; Samochocki, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
MicroRNAs are relatively new molecules that have been widely studied in recent years as to determine their exact function in the human body. It is suggested that microRNAs control approx. 30% of all genes, making them one of the largest groups that control the expression of proteins. Various functions of miRNAs have already been described. In skin diseases, there are more and more studies describing an altered expression of microRNAs in the skin or serum. Relatively little is known about the function of these molecules in atopic dermatitis, which prompted us to gather current reports on this subject.